Description of adults and immature stages of Antipodoecia Mosely from Australia and synonymy of the families Antipodoeciidae and Anomalopsychidae (Insecta: Trichoptera) - Clair, Rosalind M. St; Dean, John C.; Flint, Oliver S. Jr (Zootaxa, 2018)
The female, larva, and pupa of Antipodoecia Mosely from Australia are described, males re-examined and briefly described. Similarities with other trichopteran families are discussed. Based on morphological synapomorphies of males, females, pupae, and larvae, we infer that the genera Antipodoecia, Anomalopsyche, and Contulma share an immediate common ancestor, although relationships among these genera remain unresolved. Consequently, the Neotropical family Anomalopsychidae is a junior synonym of Antipodoeciidae from Australia.